Konsep Diri Akademik Siswa Tunaprestasi dan Terapi Perlakuan Kognitif Pada Siswa Sekolah Dasar - Tarmidi; Akbar-Hawadi, Reni (Faculty of Psychology, Universitas Surabaya, 2009)
Having a negative academic self concept is one of the main characteristics of underachiev- ing students. This article discusses cognitive behavior therapy (CBT) as a technique to improve un- derachieving students’ self concept. In this case study, CBT was given to one sixth grade student i- dentified as an underachiever. Self concept was measured using four items. After nine sessions of CBT, there was improvement in one out of the four measures of self concept. Konsep diri akademis yang buruk adalah ciri utama siswa tunaprestasi (underachiever). Ar- tikel ini membahas terapi perilakuan kognitif (cognitive behavior therapy/CBT) sebagai teknik untuk memperbaiki konsep diri siswa tunaprestasi. Dalam studi kasus ini, CBT diterapkan pada seorang sis- wa kelas enam SD yang diidentifikasi sebagai siswa tunaprestasi. Setelah sembilan sesi CBT, siswa tersebut mengalami peningkatan konsep diri pada satu di antara emjpat pernyataan yang mengukur konsep diri akademik.